Education in times of the Argentine Confederation - Bustamante, Jose (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2018)
This paper search two facets of the educational policy developed under the government of the Argentine Confederation in the 1850s. On one hand, traces of the Alberdian project are recovered, their modulations in the formulation of the fifth article of the constitution of 1853, as well as the notes introduced by the reform of 1860. Later study fiscal and educational aspects of that government; the payment orders of the Department of Justicia, Culto e Instrucción Pública during the period between 1856 and 1860 are analyzed for that purpose.